Masters of small worlds : yeoman households, gender relations, and the political culture of the Antebellum South Carolina Low Country - McCurry, Stephanie (Oxford University Press, 1995)
The book examines the yeomanry in the South Carolina Low Country before the Civil War. It focuses on the relationship between the yeomanry - the small farmers - and the planters, with whom they had strong ideological ties. The book deals with gender and class issues as well.; This book is intended for those interested in Antebellum Southern US Society.